Using positron-emission tomography–computed tomography for predicting radiotherapy-induced tumor regression in carcinoma esophagus in an Indian population - Singh, Sankalp; Bisht, Niharika; Sarin, Arti; Kumar, A. V. S.; Gupta, Samir; Kapoor, Amul; Mishra, Prabha (World Journal of Nuclear Medicine, 2019)
Carcinoma esophagus is a common malignancy of the Indian subcontinent. The role of positron-emission tomography–computed tomography (PET-CT) in the assessment of response to radiotherapy has been widely studied and accepted. However, its precise use as a predictive tool for actual histopathological response to radiotherapy needs further evaluation, especially in an Indian population. The aim of this study was to identify a quantum of metabolic response on PET-CT that can also predict for a good pathological response. Forty-four patients of carcinoma esophagus treated with neoadjuvant chemoradiotherapy followed by surgery were included in the study. All patients underwent a PET-CT before starting treatment as well as at 4–6 weeks after completion of radiotherapy. The percentage change in pre and posttreatment maximum standardized uptake value (SUVmax) value (ΔSUV%) of the primary tumor was correlated against histopathological tumor regression grade (TRG) as per the Mandard's system. Seventy-five percent of the patients with a significant metabolic response, i.e., a ΔSUV% of 60% or more, also had a good pathological response to treatment. Thus, by considering a ΔSUV% of 60%, we could predict for a good pathological response (TRG of 1 or 2) to chemoradiotherapy in our patient set with a sensitivity of 95.45% and a specificity of 72.72%.
Keywords: Carcinoma esophagus; positron-emission tomography–computed tomography; radiotherapy